Simplified Microchip Electrophoresis for Rapid Separation of Urine Proteins. Issue 2 (6th January 2014) - Song, Hongwei; Wang, Huimin; Ju, Saoqing; Jin, Qinghui; Jia, Chunping; Cong, Hui
<x xml:space="preserve">Abstract</x> Background Urine protein test has been widely used in clinics, but to determine the type of proteinuria is usually difficult due to technical limitations. Methods In the current study, a rapid and simple method to separate and determine urine proteins by a microchip electrophoresis (ME) system has been developed in which only 4 min are required. Results Optimal separation conditions have been established by using 15 s injection time at 500 and 1, 500 V separation voltage in 75 mmol/l borate buffer containing 0.8 mmol/l calcium lactate and 1% ϕ ethylamine (pH 10.55). Relative standard deviation (RSD) of migration time with purified human albumin and human transferring was 2.68% and 2.24%, and RSD of the peak area was 5.85% and 4.96%, respectively. The linear detection range was 1.0–15.0 g/l for purified human albumin and 1.0–10.0 g/l for human transferrin, with the same detection limit (S/N = 3) of 0.4 g/l. Finally, comparing to conventional agarose gel electrophoresis, the same results were obtained by using ME by testing clinical samples including 60 selective proteinuria, 105 nonselective proteinuria, and 6 overflow proteinuria. Conclusion This newly established ME could have broad applications to determine the type of proteinuria in clinics.